PATIENT CENTEREDNESS IN HEALTH CARE: PERSPECTIVES FROM AN EMPIRICAL INVESTIGATION - G, Rejikumar; Ks, Archana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objective of this study was to examine the formation of wellness perceptions and satisfaction from antecedents that explain various attributes regarding service quality perceptions about doctors by patients. The topic is of contemporary relevance as health-care firms are reengineering their competencies to deliver personalized health services to for unmatched experience to develop long-term relationships with patients. Methods: Responses from 280 patients about service quality attributes of doctors, wellness perceptions, and their satisfaction are collected using a structured questionnaire. An exploratory factor analysis was performed using SPSS. 20 to identify significant dimensions of doctor's service quality. The theoretical model developed with these dimensions, wellness perceptions, and patient satisfaction was estimated using partial least square-based structural equation modeling approach to test hypotheses about linkages among these constructs. Results: The dimension structure of doctor's service quality contained constructs such as price affordability of medicines,â€ quality of diagnosis,â€ interaction quality of doctor,â€ appropriateness of tests prescribed,â€ and quality of usage prescriptions.â€ These service quality dimensions of doctor significantly develop wellness perceptions and satisfaction among patients. Wellness perceptions act as a mediator in satisfaction development. Conclusions: Patient satisfaction and wellness perceptions are of primary importance in improving service quality in health care and to remain competitive. The health-care firms should train their professionals to interact with the patients more efficiently by adhering to the philosophy of patient centeredness in their service process.